Using solar radiation pressure to maneuver a spacecraft in the triple asteroid 2001SN263 - Silva Neto, J. B.; Sanchez, D. M.; Prado, A. F.B.A.; Formiga, J. K.S. [UNESP] (My University, 2016)
The number of missions which with an asteroid as a target has increased and this type of exploration will become even more frequent in the future. Space missions require high costs and methods that may reduce them should be studied. An alternative is the use of solar radiation pressure, using a solar sail or similar devices. This study presents a solution for the final phase of the Aster mission, which aims to collide a probe with the surface of the body Alpha of the system 2001SN263 using solar radiation pressure. As noted during the study, the low gravity of the system makes it very sensitive to solar radiation pressure. The high angular velocity of Gamma around Alpha causes collisions and involuntary gravity assisted maneuvers, which are obstacles in the search of initial conditions for the use of such devices.